The roles of dental therapists as frontline clinicians - Arua Oko, Samuel; Ngwu, Chika C.; Agbo, Emmanuel E.; Silas, Haggai; Ucheka, Promise I. (Orapuh Journal, 2021)
Dental therapists are primary oral healthcare professionals who are trained and licensed to perform basic clinical, educational, and therapeutic services to patients, including children and young adults. As members of the dental team, dental therapists in several countries work at different levels of the healthcare system but primarily in settings that serve low-income, uninsured and underserved populations. They also work in areas with a shortage of dental health professionals as the first point of call within their scope of practice and competence. This study analysed the roles of dental therapists as frontline clinicians and how good oral health policies can help harness the skills of dental therapists in addressing the global oral health problems prevalence. Also, the perspectives on dental therapists as frontline clinicians in New Zealand, the United State (US), the United Kingdom (UK), and Nigeria were reviewed for a better understanding of the global view. We searched PubMed, Google Scholar, MEDLINE, Cochrane Library, and Microsoft Academic databases for adequate information. Evidence has shown how resourceful dental therapists are in promoting good oral health and delivering competent preventive and restorative treatments to people.